Genome‐wide scan of long noncoding RNA single nucleotide polymorphisms and pancreatic cancer susceptibility. Issue 11 (3rd February 2021) - Corradi, Chiara; Gentiluomo, Manuel; Gajdán, László; Cavestro, Giulia Martina; Kreivenaite, Edita; Di Franco, Gregorio; Sperti, Cosimo; Giaccherini, Matteo; Petrone, Maria Chiara; Tavano, Francesca; Gioffreda, Domenica; Morelli, Luca; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is projected to become the second cancer‐related cause of death by 2030. Identifying novel risk factors, including genetic risk loci, could be instrumental in risk stratification and implementation of prevention strategies. Long noncoding RNAs (lncRNAs) are involved in regulation of key biological processes, and the possible role of their genetic variability has been unexplored so far. Combining genome wide association studies and functional data, we investigated the genetic variability in all lncRNAs. We analyzed 9893 PDAC cases and 9969 controls and identified a genome‐wide significant association between the rs7046076 SNP and risk of developing PDAC ( P = 9.73 × 10 −9 ). This SNP is located in the NONHSAG053086.2 ( lnc‐SMC2‐1 ) gene and the risk allele is predicted to disrupt the binding of the lncRNA with the micro‐RNA (miRNA) hsa‐mir‐1256 that regulates several genes involved in cell cycle, such as CDKN2B . The CDKN2B region is pleiotropic and its genetic variants have been associated with several human diseases, possibly though an imperfect interaction between lncRNA and miRNA. We present a novel PDAC risk locus, supported by a genome‐wide statistical significance and a plausible biological mechanism. Abstract : What's new? Long non‐coding RNAs (lncRNAs) are thought to contribute to cancer development. Here, the authors searched for new lncRNA variants that are associated with risk of pancreatic ductal adenocarcinoma (PDAC). From analysis of 15, 000 individuals, they obtained 67 variants associated with PDAC risk. Some of these were located in genes previously associated with PDAC, an outcome which not only validates the method but could shed light on the functional relevance of these genes. The strongest association was to a variant in the lnc‐SMC2‐1 gene, and the risk allele is predicted to disrupt cell cycle regulation.